The Development of Early Childhood Curriculum to Enhance Life Skills through Design Thinking Process - Lehmongkol, Thayanee; Hirunchalothorn, Piyanan; Samahito, Chalatip (Journal for Developing the Social and Community, 2026)
Background and Aims: Early childhood development lays a critical foundation for lifelong learning and well-being. Promoting life skills is essential for young children to adapt to changing social contexts. However, integrating life skills systematically into school-based curricula remains a challenge. Design Thinking, which emphasizes understanding users’ needs, problem definition, ideation, prototyping, and iterative improvement, offers a practical framework for curriculum development. This study aimed to: (1) assess the needs of school administrators and early childhood teachers regarding curriculum development; and (2) develop a school-based early childhood curriculum to promote learners’ life skills through the design thinking process. Methodology: This study employed a Research and Development approach conducted in two phases, using the Design Thinking Process as the research framework. Phase 1 focused on assessing the needs of school administrators and early childhood teachers in curriculum development through meeting and focus group discussions. The informants included one municipal administrator, two school principals, and eleven early childhood teachers. The research instrument was a focus group recording form. Phase 2 involved the development of an early childhood curriculum. The informants included two school principals and eleven early childhood teachers. The research instruments consisted of a reflective focus group recording form and a classroom observation form. Data from both phases were analyzed using content analysis. Results: The needs assessment showed that administrators and teachers recognized the importance of life skills development. School contexts, family background, parental involvement, and teacher readiness were key influencing factors. Teachers expected children to develop thinking, communication, emotional regulation, and social skills, and needed a clear, flexible, and practice-oriented curriculum. The developed curriculum integrated four life skill: social, emotional, cognitive, and communication. Its key components included curriculum focus, structure, learning units, learning activities, and assessment approaches, all aligned with local contexts and the Early Childhood Curriculum B.E. 2568 (2025). When implemented, teachers adopted more active learning approaches, allowing children to think, plan, and solve problems independently. Interdisciplinary integration and the use of open-ended questioning were enhanced. Additionally, reflective practices and collegial supervision fostered teachers’ professional learning communities and continuously supported the development of children’s life skills. Conclusion: Developing life skills–enhancing curriculum through the Design Thinking process enabled a context-responsive and systematic approach to curriculum design. The process supported teachers in organizing meaningful learning experiences and contributed to the sustainable development of young children’s life skills.